2018
DOI: 10.21276/ijcmr.2018.5.8.19
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Villous Hypervascularity and Chorangiosis at Different Maternal Hemoglobin Levels

Abstract: Introduction: Placenta has a remarkable reserve capacity to survive in the harmful environment, but some of the damaging factors, especially maternal anemia may have negating effects on placenta which might compromise the fetal well-being. Decreased hemoglobin level in pregnancy is associated with villous hypervascularity and chorangiosis, which can be assessed for diagnostic purposes because it has been considered as a result of placental hypoxia caused by maternal anemia. The objective of this study is to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The study revealed that HV is prominent with increased incidence of anaemia. 33 36,37 A twin study piloted by Jaiman et al, observed that there was defective villous maturation due to hypoxia. 38 Morgan et al, in their study observed in terminal villi there was significant hyper maturity.…”
Section: Raghuveer Et Al Histopathology Of Placentae In Pre-eclampsiamentioning
confidence: 99%
“…The study revealed that HV is prominent with increased incidence of anaemia. 33 36,37 A twin study piloted by Jaiman et al, observed that there was defective villous maturation due to hypoxia. 38 Morgan et al, in their study observed in terminal villi there was significant hyper maturity.…”
Section: Raghuveer Et Al Histopathology Of Placentae In Pre-eclampsiamentioning
confidence: 99%